2000
DOI: 10.2307/3236774
|View full text |Cite
|
Sign up to set email alerts
|

Spatial micro‐patterns in the steppe of Tierra del Fuego induced by sheep grazing

Abstract: Abstract. In the Festuca gracillima tussock steppe of northern Tierra del Fuego there is a physiognomic pattern at the community scale composed of a matrix of tussocks, scrub patches of Chiliotrichum diffusum and lawn patches. In this paper we compared floristic composition, soils, microclimate and sheep use of these three types. Species composition greatly differed among physiognomic types. Lawn patches showed the highest diversity and maximum cover of exotics, grazing escape growth forms and species of high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 31 publications
2
37
0
1
Order By: Relevance
“…Yet, few studies have included vegetation analysis at the landscape level in our study area, and most of them have focused on the understory plants of Nothofagus forests. Open lands, however, are know to present higher richness, as well as the northern steppe grasslands of Tierra del Fuego (Collantes et al 1999;Posse et al 2000). Understory Nothofagus forests richness of our study was comparable with previous studies (51 species) in primary (Lencinas et al 2008) and managed forests of Tierra del Fuego, but higher (35 species) than those described by Martínez Pastur et al (2002) for shelterwood cuts.…”
Section: Discussionsupporting
confidence: 86%
“…Yet, few studies have included vegetation analysis at the landscape level in our study area, and most of them have focused on the understory plants of Nothofagus forests. Open lands, however, are know to present higher richness, as well as the northern steppe grasslands of Tierra del Fuego (Collantes et al 1999;Posse et al 2000). Understory Nothofagus forests richness of our study was comparable with previous studies (51 species) in primary (Lencinas et al 2008) and managed forests of Tierra del Fuego, but higher (35 species) than those described by Martínez Pastur et al (2002) for shelterwood cuts.…”
Section: Discussionsupporting
confidence: 86%
“…Increased heterogeneity induced by patch grazing has been found in a wide range of ecosystems with diVerent types of herbivores (McNaughton 1984;Ring et al 1985;McNaughton et al 1997;Cid and Brizuela 1998;Pastor et al 1998;Posse et al 2000;Augustine 2004). Adler et al (2001) proposed that patch grazing typically involves repeated grazing of small areas promoted by a positive feedback between grazing and forage quality (e.g., higher than average nitrogen content in regrowth; Crawley 1983) or conWnement of herbivores to areas oVering relative security from predators.…”
Section: Discussionmentioning
confidence: 98%
“…Pastor et al (1998) quantified the spatial heterogeneity of both grazing and vegetation, and demonstrated that spatial heterogeneity in consumption by moose created similar spatial heterogeneity in vegetation. Eight studies (Bakker et al 1983;Coppock et al 1983b;McNaughton 1984;Ring et al 1985;Kellner and Bosch 1992;Lutge et al 1996;Cid and Brizuela 1998;Posse et al 2000), representing seven different ecosystems, documented patch grazing by domestic or wild ungulates. Presumably because of positive feedbacks with forage quality (Hobbs and Swift 1988), the grazers foraged in previously grazed areas, producing dramatic changes in vegetation structure and sometimes composition.…”
Section: Increases In Spatial Heterogeneity Following Grazingmentioning
confidence: 97%